(untitled) (Indonesian Tax Justice Review, 2025)
The expansion of digital platforms has fundamentally altered consumption patterns and challenged conventional VAT collection mechanisms. This paper examines Indonesia’s policy requiring digital marketplaces to collect and remit VAT on behalf of sellers. Using doctrinal and policy analysis, the study evaluates the effectiveness and equity implications of this regime for platform operators, small sellers, and consumers. The findings indicate that marketplace-based VAT collection significantly improves compliance and reduces revenue leakage in cross-border digital transactions. However, the policy also shifts administrative burdens onto platforms and small merchants, potentially exacerbating inequalities within the digital economy. The paper argues that VAT reforms targeting digital platforms must balance efficiency gains with taxpayer equity. The global contribution of this study lies in offering a concrete policy case from a developing economy addressing digital VAT challenges. Indonesia’s experience provides transferable lessons for countries seeking to tax digital consumption while preserving inclusivity. The study contributes to global tax justice literature by demonstrating that digital VAT design should incorporate proportional compliance obligations and targeted support mechanisms for small economic actors.